Remittances and Vulnerability in Developing Countries - Bettin, Giulia (IMF Working Papers; Working Paper ;, 2014)
This paper examines how international remittances are affected by structural characteristics, macroeconomic conditions, and adverse shocks in both source and recipient economies. We exploit a novel, rich panel data set, covering bilateral remittances from 103 Italian provinces to 107 developing countries over the period 2005-2011. We find that remittances are negatively correlated with the business cycle in recipient countries, and increase in response to adverse exogenous shocks, such as natural disasters or large declines in the terms of trade. Remittances are positively correlated with economic conditions in the source province. Nevertheless, in the presence of similar negative shocks to both source and recipient economies, remittances remain counter-cyclical with respect to the recipient country.